2019
DOI: 10.5267/j.msl.2019.7.024
|View full text |Cite
|
Sign up to set email alerts
|

The role of creative self-efficacy, transformational leadership, and digital literacy in supporting performance through innovative work behavior: Evidence from telecommunications industry

Abstract: In the current technology shifting era, technology plays an essential function that determines the continuity of the industry. The current technology advancements empower companies to produce creativity and innovation to serve customer needs and expectation. To deliver this challenge, it requires the continuous breakthrough and innovation. To create organization innovation, employee plays the main key, as the main source and the executor of innovation. The organizational environment in knowledge-based industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 14 publications
1
12
0
2
Order By: Relevance
“…Chiang et al (2014) emphasizes that individuals with high CSE tend to be sensitive to positive stimuli and set goals. Similar results were obtained by Santoso et al (2019) and the relationship of CSE with creative and transformational leadership, digital literacy was examined. Therefore, the findings of this study do not coincide with the results in the literature.…”
Section: Discussionsupporting
confidence: 71%
“…Chiang et al (2014) emphasizes that individuals with high CSE tend to be sensitive to positive stimuli and set goals. Similar results were obtained by Santoso et al (2019) and the relationship of CSE with creative and transformational leadership, digital literacy was examined. Therefore, the findings of this study do not coincide with the results in the literature.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies have suggested that the style adopted by a leader plays an important role in enhancing contextual factors that drive creativity-related work outcomes (Shalley and Gilson, 2004;Amabile et al, 2005;Alameri et al, 2019;Royston and Reiter-Palmon, 2019;Santoso et al, 2019). Therefore, it is possible for transformational leaders to spark creative and independent thinking skills in employees by promoting their CSE (Gumusluoglu and Ilsev, 2009;Khalili, 2016;Le et al, 2018).…”
Section: Transformational Leadership and Csementioning
confidence: 99%
“…Dengan perkembangan zaman, penelitian studi menunjukan luasnya teori inovatif, terutama di tingkat individu atau tingkat karyawan dari faktor perspektif manusia. Literatur terkini tentang inovasi difokuskan pada eksplorasi bagaimana perilaku pemimpin dan gaya, atau dampak keterampilan manajemen dapat mempengaruhi perilaku kerja inovatif anggota (Santoso et al, 2019). Bank Perkreditan Rakyat (BPR) merupakan bank yang melaksanakan kegiatan usaha secara konvensional dan didasarkan prinsip syariah yang kegiatannya tidak melibatkan jasa dalam lalu lintas pembayaran.…”
Section: Pendahuluanunclassified
“…Pada pengujian hipotesa ini, didapatkan bahwa pada nilai T statistic 7.217 dan P-value 0.000 yang menunjukkan bahwa terdapat pengaruh positif antara transformational leadership dengan innovative behavior. Pengujian tersebut didukung oleh penelitian (Widodo & Mawarto, 2020), (Li et al, 2018), (Afsar & Umrani, 2019), (Torres et al, 2017), (Margana et al, 2019, (Santoso et al, 2019) (A. M. Khan et al, 2019) menjelaskan bahwasannya gaya kepemimpinan transformasional mempengaruhi perilaku organisasi, memberikan dukungan motivasi yang dalam menginspirasi karyawannya untuk mencapai etos kerja yang tinggi yang memberikan dampak positif pada perilaku inovatif. inovatif karyawan dalam perusahaan yang mana gaya pembawaanya untuk inovasi.…”
Section: H5 : Transformational Leadership Terdapat Pengaruh Positif T...unclassified